Ante-mortem detection of chronic wasting disease in recto-anal mucosa-associated lymphoid tissues from elk (Cervus elaphus nelsoni) using real-time quaking-induced conversion (RT-QuIC) assay: A blinded collaborative study. Issue 6 (2nd November 2017) - Manne, Sireesha; Kondru, Naveen; Nichols, Tracy; Lehmkuhl, Aaron; Thomsen, Bruce; Main, Rodger; Halbur, Patrick; Dutta, Somak; Kanthasamy, Anumantha G.
ABSTRACT: Prion diseases are transmissible spongiform encephalopathies (TSEs) characterized by fatal, progressive neurologic diseases with prolonged incubation periods and an accumulation of infectious misfolded prion proteins. Antemortem diagnosis is often difficult due to a long asymptomatic incubation period, differences in the pathogenesis of different prions, and the presence of very low levels of infectious prion in easily accessible samples. Chronic wasting disease (CWD) is a TSE affecting both wild and captive populations of cervids, including mule deer, white-tailed deer, elk, moose, muntjac, and most recently, wild reindeer. This study represents a well-controlled evaluation of a newly developed real-time quaking-induced conversion (RT-QuIC) assay as a potential CWD diagnostic screening test using rectal biopsy sections from a depopulated elk herd. We evaluated 69 blinded samples of recto-anal mucosa-associated lymphoid tissue (RAMALT) obtained from USDA Veterinary Services. The results were later un-blinded and statistically compared to immunohistochemical (IHC) results from the USDA National Veterinary Services Laboratories (NVSL) for RAMALT, obex, and medial retropharyngeal lymph node (MRPLN). Comparison of RAMALT RT-QuIC assay results with the IHC results of RAMALT revealed 92% relative sensitivity (95% confidence limits: 61.52–99.8%) and 95% relative specificity (95% confidence limits: 85.13–99%). Collectively, our results show a potential utility of the RT-QuIC assay to advance the development of a rapid, sensitive, and specific prion diagnostic assay for CWD prions.